2020
DOI: 10.3390/diagnostics10050273
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide and Copy-Number Variants in IL4 and IL13 Are Not Associated with Asthma Susceptibility or Inflammatory Markers: A Case-Control Study in a Mexican-Mestizo Population

Abstract: Background: Asthma is a complex and chronic inflammatory airway disease. Asthma’s etiology is unknown; however, genetic and environmental factors could affect disease susceptibility. We designed a case-control study aimed to evaluate the role of single-nucleotide polymorphisms (SNP), and copy-number variants (CNV) in the IL4 and IL13 genes in asthma susceptibility and their participation in plasma cytokine levels depending on genotypes Methods: We include 486 subjects, divided into asthma patients (AP, n = 141… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Although it has been reported that some genes involved in inflammation are associated with respiratory diseases [ 87 , 88 , 89 , 90 , 91 , 92 ], investigations regarding genetic factors involved in the susceptibility and severity are scanty. Two primary examples in inflammatory response genes, where genetic variability is associated with an altered phenotype, are TNF-α and IL-1β; both are pleiotropic modulators critical in regulating inflammation.…”
Section: Genetic Variants and Influenza A H1n1 Virus Infectionmentioning
confidence: 99%
“…Although it has been reported that some genes involved in inflammation are associated with respiratory diseases [ 87 , 88 , 89 , 90 , 91 , 92 ], investigations regarding genetic factors involved in the susceptibility and severity are scanty. Two primary examples in inflammatory response genes, where genetic variability is associated with an altered phenotype, are TNF-α and IL-1β; both are pleiotropic modulators critical in regulating inflammation.…”
Section: Genetic Variants and Influenza A H1n1 Virus Infectionmentioning
confidence: 99%